Antimicrobial and antiseptic strategies in wound management. Issue 1 (December 2013) - Daeschlein, Georg
Abstract Wounds, especially chronic wounds, represent a global problem costing millions of dollars per year in developed countries and are characterised by microbial complications including local or overt infection, delayed healing and spread of multiresistant germs. Therefore, antimicrobial wound management is a major challenge that continues to require new solutions against microbes and their biofilms. As systemic antibiotics can barely penetrate into wound biofilms and topically applied ones can easily lead to sensitisation, antisepsis is the method of choice to treat germs in wounds. This brief review discusses the role of antiseptics in reducing bioburden in chronic wounds. Balancing antimicrobial potency and tolerability of antiseptic procedures is critical in wound therapy. However, antiseptics alone may not be able to achieve wound healing without addressing other factors regarding the patient's general health or the wound's physical environment. Although the precise role of bioburden in chronic wounds remains to be evaluated, planktonic as well as biofilm‐bound microbes are indications for antiseptic intervention. Octenidine dihydrochloride and polyhexanide are the most effective, as well as best tolerated, antiseptics in wound management today, and new strategies to reduce bacterial wound burden and support the body's immune response are being developed.